Important considerations in adolescent health maintenance: long-acting reversible contraception, human papillomavirus vaccination, and heavy menstrual bleeding. Issue 6 (December 2016) - Brodie, Nicola; Silberholz, Elizabeth A.; Spector, Nancy D.; Pattishall, Amy E.
Abstract : Purpose of review: The present article addresses recent research related to three key facets of adolescent preventive care and health maintenance: long-acting reversible contraception, human papillomavirus vaccination, and heavy menstrual bleeding. Recent findings: Recent studies suggest that long-acting reversible contraception use results in significantly lower rates of unintended pregnancies, and is well tolerated by nulliparous adolescent females. Additionally, a strong recommendation from a pediatric primary care provider is extremely effective in ensuring human papillomavirus vaccination prior to sexual debut. Finally, heavy menstrual bleeding is often under-recognized in adolescents, and evaluation and treatment of these patients are variable. Summary: Based on the recent literature findings, the pediatric primary care provider should be encouraged to, first, recommend long-acting reversible contraception for prevention of unintended pregnancy in adolescent patients; second, strongly endorse vaccination to protect against human papillomavirus in all patients prior to sexual debut; and, third, screen adolescent females for signs and symptoms of heavy menstrual bleeding.